The development of Chinese education in Malaysia, 1952–1975: political collaboration between the Malaysian Chinese Association and the Chinese educationists - Tan, Yao Sua; Teoh, Hooi See (Taylor & Francis, 2015)
This paper examines the development of Chinese education in Malaysia from 1952 to 1975, focusing on the political collaboration between the Malaysian Chinese Association (MCA) and the Chinese educationists to advance the cause of Chinese education instead of the usual macro policy analysis. This collaboration was compounded by the different stand adopted by the MCA and the Chinese educationists on issues relating to Chinese education. This different stand reflected the MCA’s political limitations to advance the cause of Chinese education. The MCA had to abide by the elite accommodation model adopted by the coalition government since it was a partner of this coalition. Such an accommodative approach could not meet the assertive demand of the Chinese educationists on issues relating to Chinese education. Meanwhile, the political collaboration between the MCA and the Chinese educationists was also constrained by internal conflict within the MCA that compromised the interests of Chinese education.